Better Loans or Better Borrowers? : Impact of Meso-Credit on Female-Owned Enterprises in Ethiopia - Alibhai, Salman (World Bank, Washington, DC, 2018)
This paper explores the impact of large, individual-liability loans on the growth of women-owned microenterprises in Ethiopia. Traditionally, microfinance institutions in Ethiopia have primarily catered to female enterprises with group lending schemes that provide very small loans. The limitations of this model are two-fold: in addition to these micro-loans being too small in size to fuel meaningful business growth, many of the female enterprises that are targeted with these loans face binding constraints, such as concentration in lower-growth sectors, lack of alternative job opportunities, limitations on time and mobility, and restrictive gender norms. The paper investigates the impact of credit to female entrepreneurs in a novel context, by examining larger loans, provided to growth-oriented women entrepreneurs. These entrepreneurs fall in the "missing middle" or "meso-finance" segment of the financial market because their credit needs are too large for microfinance, but not large enough for commercial banks. The paper uses a propensity score matching methodology to examine the impact of loans offered to women as part of the Women Entrepreneurship Development Project, a program funded by the World Bank International Development Association, that targets growth-oriented women entrepreneurs in Ethiopia. The results suggest that large, individual-liability loans can make a significant difference in accelerating growth in the business incomes and employment levels of women-owned enterprises.